Starting wages respond to employer's risk - Peter Berkhout; Joop Hartog (Institute for the Study of Labor (IZA), 2007)
Firms hiring fresh graduates face uncertainty on the future productivity of workers. Intuitively, one expects starting wages to reflect this. Formal analysis supports the intuition. We use the dispersion of exam grades within a field of education as an indicator of the heterogeneity that employers face. We find solid evidence that starting wages are lower if the variance of exam grades is higher and that starting wages are lower if the skew is higher: employers shift quality risk to new hires, but pay for the opportunity to catch the really good workers.
Keywords: 330; Wages; risk; ability; Berufseinstieg; Lohn; Vergütungssystem; Risikoaversion; Arbeitsproduktivität; Niederlande